Internet connectivity disruption in NR (NR) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in NR. Data sourced from IODA.
Network Disruption Incident ID: NR-2026-0006. Severity: critical. Confidence: 67%